Meta-Analysis of Tourism Development Aware Disaster Potential: Bibliographic Analysis of Disaster Management on Tourism Scope - Sakir Sakir; Bevaola Kusumasari; Suripto Suripto; Arissy Jorgi Sutan; Fairuz Arta Abhipraya (Universitas Muhammadiyah Yogyakarta, 2025)
This study presents a bibliometric analysis of disaster management in the tourism sector over the past five years, based on data retrieved from the Scopus database. While previous research has emphasized the vulnerability of the tourism industry to disasters and the need for preparedness, there remains a limited exploration of theoretical frameworks and localized perspectives in this field. This study addresses this gap by examining global and local trends in disaster awareness within tourism destinations. Employing a qualitative approach through a systematic literature review, the research utilizes VOSviewer and Scopus analytical tools to map developments in the field. The findings reveal a growing scholarly interest in emerging topics such as post-COVID-19 recovery strategies and sustainable tourism development. The dominance of social science disciplines in the literature underscores their crucial role in informing policy and practice. Notably, 2023 marked the peak in publication output, with Indonesia emerging as a leading contributor reflecting its dual context of rich tourism potential and high disaster vulnerability. Despite this, previous studies have often neglected the integration of local wisdom and cultural values, which are essential for effective community-based disaster management. The novelty of this study lies in its focus on disaster management through a community-based tourism lens, particularly within the context of Yogyakarta. It recommends the development of localized disaster management models that actively involve community participation and draw upon indigenous knowledge and practices to enhance tourism resilience.